2012
DOI: 10.1515/jbcpp-2012-0026
|View full text |Cite
|
Sign up to set email alerts
|

Yoyo Bitters, a polyherbal formulation influenced some biochemical parameters in Wistar rats

Abstract: In light of this, caution and adherence to dosage prescription is strongly advised. This study is a contribution to scientific knowledge on the safety/toxicity profile of Yoyo Bitters among the growing list of Nigerian herbal remedies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Alteration in body weight and/or organ to body weight ratio has been shown to imply toxicity arising from exposure to a toxicant [24, 25]. No appreciable weight change was recorded for all treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in body weight and/or organ to body weight ratio has been shown to imply toxicity arising from exposure to a toxicant [24, 25]. No appreciable weight change was recorded for all treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Such certification would need to be disseminated to the general populace, through mass media and public enlighten programmes. Although, animal studies were undertaken on the safety of Jobelyn® and Yoyo cleanser bitters® when used at recommended doses32,33, a randomised clinical trial is required in human to corroborate this claim.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have demonstrated the need to subject some of the herbal preparations through a scientific validation process to ascertain their health benefits [7,8]. Therefore, this study was designed to evaluate the antioxidant and anti-inflammatory properties of the abovementioned polyherbal preparation: Oroki herbal, Swedish bitters and Yoyo bitters with the rationale to proffer a scientific explanation for the local use of these formulations.…”
Section: Introductionmentioning
confidence: 99%